2021
DOI: 10.3390/ijerph182010832
|View full text |Cite
|
Sign up to set email alerts
|

Relationships, Decisions, and Physical Effort in the Marro Traditional Sporting Game: A Multimodal Approach

Abstract: The purpose of this study was to examine the players’ decisions-making in Marro (a Traditional Sporting Game) through a multimodal approach. Each player’s decision-making assumes specific accelerations and decelerations associated with different effort. The research objectives were: (i) to study the decision-making associated with the roles of Hunter and Hare; (ii) to know the physical effort by the roles (Hunters and Hares); (iii) to reveal T-Patterns in the multimodal strategic approach (integrated with deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
6
0
3
Order By: Relevance
“…Previous research shows that such practices not only are recognized as strengthening symbols of cultural identity for immigrant and native ethnicities, but also promote harmonious social relationships among individuals from different origins and traditions even in communities without immigrants or indigenous peoples ( Román, 2010 ; Carter-Thuillier et al, 2018 ; Berti and Lapiccirella, 2019 ; Puente-Maxera et al, 2020 ). In short, TSG are cultural traditions and symbols ( Martín-Martínez et al, 2021 ) that allow, through physical-playful experiences, the conservation of identities and the positive exchange between them based on corporeality ( Parlebas, 2020 ). Therefore the use of TSG in the classroom is a concrete way of recognizing the different cultures present in the context, assuming then, that human action and motricity are indivisibly linked with culture ( Martínez-Santos et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research shows that such practices not only are recognized as strengthening symbols of cultural identity for immigrant and native ethnicities, but also promote harmonious social relationships among individuals from different origins and traditions even in communities without immigrants or indigenous peoples ( Román, 2010 ; Carter-Thuillier et al, 2018 ; Berti and Lapiccirella, 2019 ; Puente-Maxera et al, 2020 ). In short, TSG are cultural traditions and symbols ( Martín-Martínez et al, 2021 ) that allow, through physical-playful experiences, the conservation of identities and the positive exchange between them based on corporeality ( Parlebas, 2020 ). Therefore the use of TSG in the classroom is a concrete way of recognizing the different cultures present in the context, assuming then, that human action and motricity are indivisibly linked with culture ( Martínez-Santos et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the above, different authors ( Grimminger, 2011 ; Ko et al, 2015 ; Wyant et al, 2019 , 2020 ; Doidge et al, 2020 ; Siljamäki and Anttila, 2021 ) have raised the need to include intercultural competence in the training of PE teachers and Sport Coaches, because otherwise they might have initial problems in working in culturally diverse contexts and also difficulties in helping their students to acquire intercultural skills. Likewise, studies ( Carter-Thuillier et al, 2018 ; Pic et al, 2019 ; Puente-Maxera et al, 2020 ; Martín-Martínez et al, 2021 ; Lavega-Burgués et al, 2023 ; Moya-Higueras et al, 2023 ) related to TSG show that its use in the classroom represents an effective way of incorporating different cultures into the school, in addition to generating positive effects on different socioemotional and motor variables, however, the need for teachers who are sufficiently prepared in this area is also exposed for authors. Therefore, it seems essential to specifically train teachers who intend to work with the use of TSG in intercultural contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the possible approaches of our study can be done by the 360° approach used ( Lavega-Burgués et al, 2020 ; Martín-Martínez et al, 2021 ). Through an observational methodology and T-Patterns, we could find out differences pre–post test throughout the temporal distributions events ( Pic et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors applied classification trees and found that the T-pattern analyzes between girls and boys in a mixed group were unequal. This difference was mainly due to decision making (subrole variable), which had much greater predictive power than the energetic variables Martín-Martínez et al (2021). analyzed players' decision…”
mentioning
confidence: 99%